Low-Intensity Pulsed Ultrasound Therapy: A Nonsurgical Treatment Modality for Mandible Fracture Nonunion? - Abel, Adam R.; Reeve, Gwendolyn S. (Facial Plastic Surgery, 2021)
Standard treatment of mandibular nonunion includes debridement and application of maxillomandibular or rigid internal fixation techniques, with adjunctive bone grafting when necessary. Frequently described in the orthopaedic literature, low-intensity pulsed ultrasound therapy (LIPUS) is a noninvasive treatment modality used to accelerate healing of fresh fractures and established nonunions. The purpose of this study was to conduct a systematic review to determine the extent of LIPUS study in the treatment of mandibular nonunions to identify whether LIPUS represents an effective nonsurgical alternative or adjunct for nonunion management. A literature review was conducted to investigate published reports on the utilization of LIPUS in treating mandible fracture nonunions. The search yielded two randomized controlled trials demonstrating favorable healing parameters in fresh human mandible fractures treated with LIPUS, two randomized controlled trials demonstrating osteogenic differentiation in human mandibular fracture cellular components, and one study reporting improved healing at rabbit mandibular osteotomy sites. No articles published reports studying LIPUS in facial fracture nonunion were identified. This report reviews published literature on mandibular nonunions, and the evidence of LIPUS use in long bone nonunions. There are no known studies presenting LIPUS treatment of mandible fracture nonunions. However, on the basis of published orthopaedic data, LIPUS therapy could be considered as an adjunct or alternative to traditional surgical management of select mandible fracture nonunions.
Keywords: LIPUS; mandibular fractures; fracture; abnormal union